Analisis Komoditi Unggulan Tanaman Pangan Dalam Rangka Perencanaan Kawasan Agropolitan di Kota Padang - Ilham Martadona; Yeti Lis Purnamadewi; Mukhamad Najib (Universitas Teuku Umar, 2016)
Padang has a potential natural resources and land to develop the agricultural commodities, especially food crops which has total area of 23,158 hectares or 69.30 percent of total agricultural land. There are several types of food crops (rice, maize, cassava, sweet potatoes and peanuts) that cultivated in Padang and scattered in some producing regions. Based on the background of the study the purpose of this study are to analyze leading commodity of crops in order to develop agropolitan in Padang. The analytical method is Location Quotient (LQ). Based on LQ analysis shows that crop become the leading commodity in Padang is paddy. Therefore paddy is the main commodity in the development of agropolitan.